Application of an active middle ear implant in congenital middle ear malformations: A contemporary review - Vagner Antonio Rodrigues da Silva; Henrique Furlan Pauna; Guilherme Correa Guimarães; Joel Lavinsky; Thomas E. Linder; Arthur Menino Castilho (Brazilian Journal of Otorhinolaryngology)
Objective: To evaluate hearing outcomes and postoperative complications among patients with middle and external ear malformations undergoing active middle ear implantation with Vibrant Soundbridge® (VSB). Methods: Review of the literature. Studies published in English, Portuguese, or Spanish at the following databases: PubMed, MEDLINE, Scopus, Web of Science, EMBASE, and Cochrane Library were searched. The search strategy yielded a total of 141 potentially relevant studies. Of these, ten were included in this analysis. Results: The mean preoperative air conduction threshold was 66.7 ± 6.2 dB. The mean air-bone gap was 46 ± 7.7 dB. VSB implantation resulted in mean hearing gain of 40.5 ± 7.1 dB in the air-conduction thresholds among the evaluated frequencies. The speech recognition index if the Floating Mass Transducer (FMT) was placed in the short process was 86.0% ± 9.6%, with significant difference when compared to long process coupling (p = 0.035) and the round window coupling (p =  0.048). Conclusion: Bone conduction thresholds did not worsen in any of the studies included in the present review. VSB implantation resulted in a mean hearing gain of 40 dB at air conduction thresholds.